Un-covering irrigation canals as an urban renewal mechanism. The eastern edge of Zaragoza (Spain) - de la Cal Nicolás, Pablo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
With two dense districts and a large adjoining expanse of metropolitan orchards, the eastern edge of Zaragoza (Spain) is a perfect example for analyzing water flows in “irrigated cities”, where a major functioning irrigation infrastructure has survived, generally in arid climate conditions. The basic premise of water–city challenges is analyzing these agricultural systems’ potential for spatial and functional transformation strategies within a necessary urban renewal framework. The starting parameters are similar to those of other international examples whose urban strategies implemented to combat climate change have focused heavily on issues such as the storage capacity of rainwater and its urban reuse. However, in the example in question and, in general, in “irrigated cities”, more attention should be paid to “making the city’s agricultural structure more visible” by creating ecological corridors inside the city and by correcting the urban microclimate in highly dense areas with significant levels of compactness.
Keywords: Irrigation Canals; Urban Agriculture; Water Cycle; Urban Microclimate